2018
DOI: 10.1002/ar.23995
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Pancreatic Canine Fetal Cells at the Final Stage of Gestation

Abstract: The incidence of diabetes mellitus in dogs is increasing in recent years, mainly because of genetic and/or environmental factors, including endocrine disorders (like in humans); failure of suitable control of blood sugar levels, which triggers hyperglycemia; glycosuria and weight loss, which demands the development of innovative treatments to cure or treat this complex disease in dogs. The present study established for the first time a protocol to obtain and characterize cells derived from pancreas of canine f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
1
0
1
Order By: Relevance
“…There are few publications mentioning spontaneous in vivo differentiation (teratoma) using canine iPSCs, but the crucial chimera formation has not been reported yet [94]. Regarding T1DM, the isolation and characterisation of pancreatic canine foetal cells in a 2D model cell culture system were described where the expression of the pluripotent marker NANOG, the proliferation marker PCNA, and the pancreatic transcription factor PDX1 indicated that these cells could be a source of stem cell studies [135].…”
Section: Canine Culture Of β-Cellsmentioning
confidence: 99%
“…There are few publications mentioning spontaneous in vivo differentiation (teratoma) using canine iPSCs, but the crucial chimera formation has not been reported yet [94]. Regarding T1DM, the isolation and characterisation of pancreatic canine foetal cells in a 2D model cell culture system were described where the expression of the pluripotent marker NANOG, the proliferation marker PCNA, and the pancreatic transcription factor PDX1 indicated that these cells could be a source of stem cell studies [135].…”
Section: Canine Culture Of β-Cellsmentioning
confidence: 99%
“…Momen Dipol (11) Nama IUPAC (28) Trihidrooksidoboron Asam Borat (15) Nama Lain (10) Sumber (26) Struktur (12) Nama (9) Kegunaan (14) Sifat (1) Asam Boraks (4) Sasolit Asam Ortoborat (27) Borofaks…”
Section: Analisis Gapunclassified